Genetic profile of a large Spanish cohort with hypercalcemia - García-Castaño, Alejandro; Madariaga, Leire; Gómez-Conde, Sara; González, Pedro; Grau, Gema; Rica, Itxaso; de Nanclares, Gustavo Pérez; De la Hoz, Ana Belén; Aguayo, Aníbal; Martínez, Rosa; Urrutia, Inés; Gaztambide, Sonia; et al. (Frontiers in Endocrinology, 2024)
Introduction The disorders in the metabolism of calcium can present with manifestations that strongly suggest their diagnosis; however, most of the time, the symptoms with which they are expressed are nonspecific or present only as a laboratory finding, usually hypercalcemia. Because many of these disorders have a genetic etiology, in the present study, we sequenced a selection of 55 genes encoding the principal proteins involved in the regulation of calcium metabolism. Methods A cohort of 79 patients with hypercalcemia were analyzed by next-generation sequencing. Results The 30% of our cohort presented one pathogenic or likely pathogenic variant in genes associated with hypercalcemia. We confirmed the clinical diagnosis of 17 patients with hypocalciuric hypercalcemia (pathogenic or likely pathogenic variants in the CASR and AP2S1 genes), one patient with neonatal hyperparathyroidism (homozygous pathogenic variant in the CASR gene), and another patient with infantile hypercalcemia (two pathogenic variants in compound heterozygous state in the CYP24A1 gene). However, we also found variants in genes associated with primary hyperparathyroidism (GCM2), renal hypophosphatemia with or without rickets (SLC34A1, SLC34A3, SLC9A3R1, VDR, and CYP27B1), DiGeorge syndrome (TBX1 and NEBL), and hypophosphatasia (ALPL). Our genetic study revealed 11 novel variants. Conclusions Our study demonstrates the importance of genetic analysis through massive sequencing to obtain a clinical diagnosis of certainty. The identification of patients with a genetic cause is important for the appropriate treatment and identification of family members at risk of the disease.